Avaliação de contatos de pessoas com Tuberculose pulmonar no município de Três Lagoas, MS - DEMILSON CORDEIRO DA SILVA (2022)
Ministry of Health aims to reduce the incidence and mortality from tuberculosis and, for that, it establishes as one of the strategies the evaluation of contacts who regularly live with the person who has the diagnosis of the disease. The objective of this study was to describe the evaluation of household contacts of people with pulmonary tuberculosis by Primary Health Care services. This is a cross-sectional and exploratory study carried out in Três Lagoas, Mato Grosso do Sul. The study population consisted of all household contacts of people diagnosed with pulmonary tuberculosis in the municipality between 2018 and 2020. A structured instrument was developed with sociodemographic and clinical variables for index cases and contacts, as well as the actions taken by health professionals in relation to identified contacts. Data were extracted from secondary sources and analyzed using descriptive statistics (absolute and relative frequency distribution), Pearson's chi-square test or Fisher's exact test. These last two tests were used to verify the association between the actions taken with the contacts and the type of health service that monitored the index case (Basic Health Unit or Family Health Unit). Among 246 contacts recorded in the medical records of 92 index cases of tuberculosis in the municipality, 243 (98.8%) were included in the study, of which 24 (9.9%) were younger than ten years old and 219 (90.1%) had age equal to or older than ten years. Among contacts younger than ten years old, ten (41.7%) were clinically evaluated and considered asymptomatic. Among these, two (20.0%) did not undergo any exam, four (40.0%) only performed the X-ray and four (40.0%) performed the X-ray and tuberculin skin test, being non-reactive for Mycobacterium tuberculosis. Among contacts aged ten years or older, 163 (74.4%) were clinically evaluated, of which 30 (18.4%) were considered symptomatic. Among these, one (3.6%) did not undergo any examination, two (6.7%) only performed the X-ray, 25 (83.3%) performed the X-ray and sputum smear microscopy and two (6.7 %) performed these two tests and the tuberculin skin test. Among the symptomatic contacts, 18 (60.0%) were diagnosed with active TB and none with latent infection. As for the asymptomatic contacts (133), 14 (10.5%) did not undergo any examination, 96 (72.2%) underwent only the X-ray, one (0.8%) only the tuberculin skin test, 18 (13, 0%) X-ray and tuberculin skin test, three (2.3%) X-ray and sputum smear microscopy and one (0.8%) performed these two tests and tuberculin skin test. Of the 20 people who underwent the tuberculin skin test, two were positive (10%) and completed the treatment for LTBI. There was no statistically significant association between Basic Health Units and Family Health Care Units in relation to the actions taken in relation to the identified contacts. Thus, there was a failure to observe the proposed protocol for the assessment of asymptomatic contacts, due to the low performance of the tuberculin skin test and the prioritization of chest radiography. For symptomatic patients, sputum smear and chest radiography were prioritized, as recommended by the Ministry of Health, which ensured the diagnosis of the disease in about half of these contacts. Keywords: Tuberculosis, Contact Tracing, Public Health.